Tribal Traditions and Shariah in the Legal Folklore of the Music at the Digo Tribe in Africa - Kanyar, Adrienn (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
The East African Digo tribe is a young Islamic group, just a hundred years old. In addition to their unique, folk Islamic religion, they have strong tribal traditions and customs, which can be felt in all areas of their society. This duality also appears in areas of regulations in culture and music. By studying them, on the one hand, we can help preserve these special legal customs, and on the other hand, they can help us to understand how Shariah functions in young Muslim groups.